Pendekatan Reader Response Criticism terhadap Narasi Tulah di Mesir dalam Peristiwa Keluaran - Sonny Eli Zaluchu (UIN Sunan Gunung Djati Bandung, 2020)
Reader Response Criticism (RRC) is a postmodern hermeneutic approach that emphasizes meaning lies not in the hands of the writer or text but the reader's hands. With this method, the approach to obtaining meaning depends very much on the reader's experience and the extent to which he places himself in the text. The problem is when this approach used for hermeneutical scriptures, and some new meanings emerge that even outperform mainstream textual meanings. This paper contains a discussion of the RRC approach and its use in analyzing the scriptures. The narrative used is the portion of the exodus of the children of Israel from Egypt, where Elohim dropped ten plagues upon Egypt. New meaning instruments produced with this approach, such as plagues, are not merely miracle stories but products of natural phenomena. Likewise, the act of God in the plagues can be understood as an act of anger and discrimination. It can conclude that as a critical approach, the RRC method could not be entirely applied to hermeneutical scriptures because there are parts of the scriptures that must be preserved literally as part of the truth of the faith of believers. While on the other hand, the RRC is open to multiple meanings, which contradict the literal meaning in the text and context.